MGT913: Organization Theory and Design - UiTM, Faculty of Business Management (2023)
This course takes the perspective of using organization as the unit of analysis and takes the macro perspective of using theories to scientifically study organizations formally. It is meant to help candidates identify, understand, analyze and apply ideas on the various aspects of organizational design. Through an actual organization’s situational problem in any industry, candidates have the opportunity to collect data that will be utilized for applications of related models recommended for solving the problem selected. The concern is with building high performance systems to deal with a critical problem facing organizations worldwide – how to be competitive in a global marketplace. It focuses on organizational level concepts. This course reflects a dual focus on practice and theory.